2007
DOI: 10.1109/jmems.2007.892903
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Preliminary Results for LiGA Fabricated Nickel Micro Gas Chromatograph Columns

Abstract: High aspect ratio nickel microfluidic columns were fabricated using the LiGA technique. The 2-m-long 50-m-wide high aspect ratio columns will be the separation component of a handheld gas chromatograph device for detecting semivolatile and volatile compounds. As a first step, 600-m-deep electrodeposited nickel columns were fabricated. The serpentine columns were sealed and pressure-flow rate characteristics compared with the theoretical values. The response of the sealed columns was studied by running methane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…6) show a thicker coating layer and also demonstrate the pooling effect at the bottom corners of these rectangular columns. It should be noted that the pooling effect has been reported by other groups in open rectangular MEMS columns as well [5,26,27]. It is very challenging to coat MEMS-based columns with a uniform stationary phase using traditional static and dynamic techniques given that these methods were developed for capillary tubing.…”
Section: Design and Fabricationmentioning
confidence: 95%
See 1 more Smart Citation
“…6) show a thicker coating layer and also demonstrate the pooling effect at the bottom corners of these rectangular columns. It should be noted that the pooling effect has been reported by other groups in open rectangular MEMS columns as well [5,26,27]. It is very challenging to coat MEMS-based columns with a uniform stationary phase using traditional static and dynamic techniques given that these methods were developed for capillary tubing.…”
Section: Design and Fabricationmentioning
confidence: 95%
“…The use of microelectromechanical systems (MEMS) technology to realize miniaturized GCs (GCs) has been in progress at several laboratories. The development of MEMS-based separation columns, the most critical element of the system, has been the major focus of such efforts [3][4][5][6][7][8][9][10][11]. These microfabricated columns typically have rectangular cross-sections, are open type, and are fabricated using deep reactive ion etching (DRIE) or LiGA (lithography, electroplating, and molding) techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of the portable GC systems was limited due to the large volume, high power consumption of traditional GC column. As MEMS technology matures, the micro GC columns [15][16][17][18][19] have a prospect future with some advantages of small size, rapid analysis, batch production, and less power consumption. The portable system integrated with micro GC columns can provide realtime monitoring for quantification and identification analysis of environmental sample.…”
Section: Micro Gc Columnmentioning
confidence: 99%
“…In this paper, the authors reported coating a 3 m-long separation column with a very thin (100 nm -200 nm) and uniform film to achieve high separation efficiency (12,500 theoretical plates). Although microseparation columns have been traditionally fabricated on a silicon wafer, Bhushan et al [6] utilized a standardized LiGA (lithography, electroplating and molding) process to fabricate high-aspect-ratio nickel columns. In this study, 2 m-long, 50 µm-wide and 300 µm-deep metal columns were sealed using electroplating and statically coated with OV-1 polymer.…”
Section: Introductionmentioning
confidence: 99%